USE COLCHICINE IN TREATING GOUT AND HYPERURICEMIA AS ASELECTION DRUG - Oxunova Mashhuraxon Jumaboy qizi (Web of Journals Publishing, 2025)
Therapeutic strategies for gout and hyperuricemia have been subjected to systematic and formal consensus review processes and disseminated in various Rheumatology Society guidelines and in clinical quality measures. The principal immediate goal of therapy in patients with acute gout is rapid, safe improvement in pain and inflammation. Long-term objectives include limiting recurrences of acute gouty arthritis and inhibiting chronic gouty synovitis and progression to erosion and other manifestations of permanent joint damage. Treatment of both the pain and inflammation associated with acute gout is achieved with anti-inflammatory agents. Other modalities (e.g., topical ice packs, acetaminophen) are adjunctive measures.
Keywords: gout, gouty arthritis, uric acid, flare, interleukin, NSAIDs, systemic corticosteroids, colchicine, European League Against Rheumatism (EULAR).